2019
DOI: 10.3892/ol.2019.11140
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the expression of HOXC13 and its role in the prognosis of breast cancer

Abstract: The homeobox (HOX) genes, a class of transcription factors, are known to promote embryonic development and induce tumor formation. To date, the HOXA and HOXB gene families have been reported to be associated with breast cancer. However, the expression and exact role of homeobox C13 (HOXC13) in breast cancer has not yet been investigated. In the present study, the HOXC13 expression in human breast cancer was evaluated using the Oncomine database and Cancer Cell Line Encyclopedia (CCLE). Next, the Gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…13). In normal-like (MCF10A) vs. TNBC (MB231 and MB436) downregulated genes, 15 genes have been predicted in this study and their role in breast cancer have also been previously reported (TNFSF10, TMEM47, IQGAP2, FAT4, NUPR1, HOXC13, PRRX1, STC2, AC108941.2, ADAMTSL1, ARHGEF5, BNC1, CPA4, PPL, and TNFRSF10D) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (Fig. 5, Supplementary Ta-bles 6, 20, Supplementary Fig.…”
Section: Rna-seq Analysissupporting
confidence: 75%
“…13). In normal-like (MCF10A) vs. TNBC (MB231 and MB436) downregulated genes, 15 genes have been predicted in this study and their role in breast cancer have also been previously reported (TNFSF10, TMEM47, IQGAP2, FAT4, NUPR1, HOXC13, PRRX1, STC2, AC108941.2, ADAMTSL1, ARHGEF5, BNC1, CPA4, PPL, and TNFRSF10D) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (Fig. 5, Supplementary Ta-bles 6, 20, Supplementary Fig.…”
Section: Rna-seq Analysissupporting
confidence: 75%
“…HOXC13 is a member of the homeobox family, which binds to a speci c nucleotide sequence on DNA and activates or inhibits the transcription process [36][37][38].It has been reported that high expression of HOX proteins may lead to carcinogenesis [39]. The expression of HOXC13 was reported to be upregulated in several kinds of cancers, including esophageal squamous cell carcinoma, lung adenocarcinoma, breast cancer and melanoma [40][41][42][43]. Especially, aberrant expression of HOXC13 was also associated with colorectal cancer [44,45] and knockdown of HOXC12 could signi cantly inhibit colorectal cancer cell growth and result in cell cycle arrest [46].…”
Section: Discussionmentioning
confidence: 99%
“…The ADCY9 expression remarkably increased in colon tumor tissue and can be a poor prognostic factor for colon survival 42 . The HOXC13 and CSNK2B expression increase in breast cancer and play a key role in the progression of breast cancer 43,44 . The expression of cyclins regulated by HOXC13 and knockdown of this gene resulted to cell cycle arrest and apoptosis, in the colon cancer cell lines 45 .…”
Section: Discussionmentioning
confidence: 99%
“…42 The HOXC13 and CSNK2B expression increase in breast cancer and play a key role in the progression of breast cancer. 43,44 The expression of cyclins regulated by HOXC13 and knockdown of this gene resulted to cell cycle arrest and apoptosis, in the colon cancer cell lines. 45 The roles of identified miRNAs in cancer were also determined.…”
Section: F I G U R Ementioning
confidence: 99%